Enhancement of Ethanol Separation from Aqueous Solution by Adsorption Technique - Almaliky, Mazin; Roaa J. ElKheralla; Omar W. Ashour (University of Thi-Qar Journal of Science, 2025)
Because of the huge industrial development and the high dependency on fossil fuel leading to high air pollution which causes a variety diseases such as respiratory diseases and disaster of global warming all these severe results encourage the researchers to figure out an alternative fuel which has a low environmental impact, the promised one is the bioethanol. The basic process to produce bioethanol is the fermentation for biomass, the most challenging of this process is the separation of bioethanol. This work concerns with modification of bioethanol separation from simulation aqueous solution of the fermentation by adsorption method. The study assesses different types of the feedstock of the fermentation as adsorbents based on the selectivity and capacity. The capacity values via water for yellow corn, wheat bran, rice straw and wheat straw were 0.24, 0.28, 0.15 and 0.14 respectively, and the selectivity values via water were 4, 2, 3, and 2.2 respectively. The first ethanol separation stage of adsorption (after the fermenter) used sepabeads207 to purify ethanol from 10 wt% to 50 wt% used in previous study. In this study, the second separation stage was established including crushed y-corn and wheat bran ethanol purity of 60wt%. The third separation step used y-corn and rice straw to introduce a bioethanol ratio for 70wt%.